Revenue allocation for a stable democracy in Nigeria - Onwioduokit, Emmanuel Ating (Achimota : African Christian Press)
This book carefully and painstakingly examines the various options available to Nigeria regarding an equitable revenue allocation as she seeks to attain a stable democracy after several years of military rule.
Includes bibliographical references.
osa 29/09/2016, ijb 11/02/2019
Loans
Keywords: Democracy; Democracy -- Nigeria; Resource allocation; Resource allocation---Nigeria.; Nigeria